SEEG is a Safe Procedure for a Comprehensive Anatomic Exploration of the Insula: A Retrospective Study of 108 Procedures Representing 254 Transopercular Insular Electrodes. Issue 1 (9th May 2017) - Salado, Anne Laure; Koessler, Laurent; De Mijolla, Gabriel; Schmitt, Emmanuelle; Vignal, Jean-Pierre; Civit, Thierry; Tyvaert, Louise; Jonas, Jacques; Maillard, Louis Georges; Colnat-Coulbois, Sophie
Abstract: BACKGROUND: The exploration of the insula in pre-surgical evaluation of epilepsy is considered to be associated with a high vascular risk resulting in an incomplete exploration of the insular cortex. OBJECTIVE: To report a retrospective observational study of insular exploration using stereoelectroencephalography (sEEG) with transopercular and parasagittal oblique intracerebral electrodes from January 2008 to January 2016. The first purpose of this study was to evaluate the surgical risks of insular cortex sEEG exploration. The second purpose was to define the ability of placing intracerebral contacts in the whole insular cortex. METHODS: Ninety-nine patients underwent 108 magnetic resonance imaging (MRI)-guided stereotactic implantations of intracerebral electrodes in the context of preoperative assessment of drug-resistant epilepsy, including at least 1 electrode placed in the insular cortex. On postoperative computed tomography images co-registered with MRI, followed by MRI segmentation and application of a transformation matrix, intracerebral contact coordinates of the insular electrodes' contacts were anatomically localized in the Talairach space. Finally, dispersion and clustering analysis was performed. RESULTS: There was no morbidity, in particular hemorrhagic complications, or mortality related to insular electrodes. Statistical comparison of intracerebral contact positions demonstrated that whole insula exploration is possible on the left and right sides. In addition, the clustering analysis showed the homogeneous distribution of the electrodes within the insular cortex. CONCLUSION: In the presurgical evaluation of drug-resistant epilepsy, the insular cortex can be explored safely and comprehensively using transopercular sEEG electrodes. Parasagittal oblique trajectories may also be associated to achieve an optimal exploration.